JCC sebagai Komunikasi Digital Terpadu Informasi Kebencanaan di Jawa Barat - Fardiah, Dedeh; Darmawan, Ferry; Rinawati, Rini; Supaat, Viky Edya Martina; Abdullah, Sandi Ibrahim (Program Studi Ilmu Komunikasi, 2023)
In the context of disaster communication in the digital era, synergy and cooperation between stakeholders in forming a disaster management information management system is carried out using digital communication integrated with the